Level of institutional delivery service utilization and associated factors among women who gave birth in the past 12 months, Ga'an libah district, Marodijeh region, Somaliland: a community-based cross-sectional study - Mustakim Mohamed; Barkhad Aden Abdeeq; Ahmed Ismail Mohamed; Hassan Abdi Jama; Fikru Tafese; Muluneh Getachew (BMC, 2024)
Abstract Background Institutional delivery has been considered one of the important strategies to improve maternal and child health and significantly reduce birth-related complications. However, it is still low in developing countries though there are some improvements. even among the community who has access to the health institutions weather health center and hospital including Somaliland. Hence, the aim of this study was to assess the level of institutional delivery service utilization and associated factors among women who gave birth in the last 12 months in Ga'an libah district, Marodijeh region, Somaliland. Methods The community-based cross-sectional study was conducted among women who gave birth in the last 12 months from September to December 2022. A simple random sampling technique was employed to select study participants from a total of sample population. Data was collected using semi-structural administered questionnaire through interviewing women. Data was collected with online mobile data collection (Kobo collect). SPSS version 25.0 was used for data management, entering and analysis. Bivariate and multivariable logistic regression models were fitted to determine the presence of a statistically significant association between independent variables and the outcome variable with p-value < 0.05. Result Level of Institutional delivery services utilization in Ga'an libah district was 53.9% [95% Cl 48.2-59.6] gave birth at health institutions. Women who can read and write local were (AOR 2.18, 95% CI 1.08-4.56, p<0.01), Women with their husband can be capable to read and write are [(AOR = 6.95, 95% Cl 2.82-21.58, p<0.002]). Additionally, ability to cost transportation for referral [AOR 5.21, 95% Cl 2.44-11.13, p<0.001]. not good services available [AOR 0.07, 95%Cl 0.01-0.10, p<0.02]. lack of maternal health and child knowledge [AOR 0.034, 95% Cl 0.02-0.57, p<0.01]. were observed associated with level of institutional deliver services utilization. Conclusion The institutional delivery service utilization was relatively high compared to national demographic health services in the study area. A large proportion of women gave both at home without a skilled attendant. Therefore, this finding has important policy implications since changes in the cost of the health service and perceived quality would mean changes in client satisfaction as well as their choice, as well emphasize to expectant women can receive medical advice and ambulance for referrals.